CATALYSIS BY MINERAL SURFACES IMPLICATIONS FOR MO GEOCHEMISTRY IN ANOXIC ENVIRONMENTS - Vorlicek T.P.; Helz G.R. (My University, 2002)
Fixation of Mo in sulfidic environments is believed to be preceded by conversion of geochemically passive MoO42− to particle-reactive thiomolybdates (MoOxS4−x2−). In aqueous solution, these transformations are general-acid catalyzed, implying that proton donors can accelerate both the forward and reverse reactions. Here, we explore whether mineral surfaces also catalyze thiomolybdate interconversions. The rate of MoS42− hydrolysis is investigated in the presence and absence of natural kaolinite (KGa-1b) and synthetic Al2O3 and SiO2 phases. Comparison of rates achieved with these phases suggests that the Al oxyhydroxide component in kaolinite furnishes the catalytic activity. An anhydrous Al2O3 phase is catalytically inactive until hydrated (and therefore protonated). Surface kinetics with kaolinite at mildly alkaline pH are consistent with rate limitation by formation or decomposition of monomeric surface complexes; oligomeric surface intermediates may become important at MoS42− > 20 μmol/L, higher than is likely to be found in nature. The pH dependence of the kaolinite-catalyzed reaction suggests that weak-acid surface sites promote hydrolysis. Intermediate thiomolybdates or molybdate appears to compete for active sites, inhibiting MoS42− hydrolysis. Catalysis of MoOS32− hydrolysis is also observed but has not been studied systematically. Thiomolybdate hydrolysis is inhibited slightly by sulfate and more strongly by phosphate. Low NaCl concentrations (<10−2 mol/L) promote hydrolysis, but higher NaCl concentrations retard the reaction to a small extent. A mechanism is postulated involving expansion of the coordination number around Mo from 4 to 6 under the influence of the surface. The effective concentration of surface sites available to Mo in sediment pore waters is likely to be large enough to greatly accelerate thiomolybdate hydrolysis and sulfidation. Possibly this explains why Mo capture in seasonally or intermittently anoxic environments often occurs through processes operating within sediments but not in overlying waters.